2019
DOI: 10.1007/s40119-019-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

TRimetazidine as an Agent to affeCt clopidogrEl Response: The TRACER Study

Abstract: IntroductionThis prospective study aimed to determine whether trimetazidine (TMZ) alters the pharmacodynamic (PD) effects of clopidogrel.MethodsPatients with stable coronary artery disease (SCAD) (n = 24) who were actively treated with dual antiplatelet therapy (DAPT) of aspirin 81 mg daily and clopidogrel 75 mg daily were recruited. Platelet function was measured with the VerifyNow P2Y12 assay (Accriva Diagnostics, San Diego, CA, USA) and assessed before the initiation of and after 14 days of treatment with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Platelet function assays included the VerifyNow TM P2Y 12 (VN-P2Y 12 ) assay (Instrumentation Laboratory, Massachusetts, USA). The assays were performed according to standard protocols, as previously described [7][8][9]. The VN-P2Y 12 assay reports the results as P2Y 12 reaction units (PRU).…”
Section: Blood Sampling and Verifynow Tm P2y 12 Testingmentioning
confidence: 99%
“…Platelet function assays included the VerifyNow TM P2Y 12 (VN-P2Y 12 ) assay (Instrumentation Laboratory, Massachusetts, USA). The assays were performed according to standard protocols, as previously described [7][8][9]. The VN-P2Y 12 assay reports the results as P2Y 12 reaction units (PRU).…”
Section: Blood Sampling and Verifynow Tm P2y 12 Testingmentioning
confidence: 99%
“…Diabetes is implicated in accentuating platelet reactivity via a complex thrombotic milieu [ 5 ]. The study also had a relatively higher proportion of women (56%) as compared to prior studies performed by this group in a similar setting [ 6 , 10 ]. Thus, any emerging recommendations cannot be extrapolated to other populations, such as patients with ACS.…”
Section: Discussionmentioning
confidence: 90%
“…A recent East Asian systematic review suggested that low-dose ticagrelor revealed an antiplatelet efficacy similar to that of standard-dose ticagrelor, which was faster and more potent than clopidogrel, however, required further evaluation in a large-scale randomized clinical trial [ 9 ]. These findings raised the question as to whether the current recommended dose of ticagrelor is suitable for the Trinidadian population, a population often described as multiethnic and cosmopolitan, comprising an admixture of South Asian, Caribbean Black, East Asian, Arabic, and Caucasian ancestries [ 6 , 10 ]. Therefore, we conducted this exploratory pilot study to assess the antiplatelet PD effect of low-dose ticagrelor in a Trinidadian subpopulation with stable coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…Десять років тому був описаний негативний вплив блокатора протонної помпи омепразолу на зменшення антитромбоцитарної активності клопідогрелю in vitro [27]. Результати нещодавно опублікованого дослідження TRACER (2019) показали істотне погіршення антитромбоцитарного потенціалу клопідогрелю в разі додавання триметазидину [28]. Останній вважається препаратом метаболічної дії, який в умовах ішемії пригнічує активність 3-кетоацил-коензим-А-тіолази в клітинах міокарда [29].…”
unclassified